The Effect of Biological Asset Intensity, Green Accounting Implementation, and Total Asset Turnover on Financial Performance : A Study of Agricultural Companies Listed on the Indonesia Stock Exchange, 2020–2024 - Muammar Qadafi Muhajir; Abdul Rahman Mus; H. Hajering (Manunggal Halim Jaya, 2026)
This study aims to examine and analyze the effects of Biological Asset Intensity, Green Accounting Implementation, and Total Asset Turnover on the Financial Performance of agricultural companies listed on the Indonesia Stock Exchange during 2020–2024. The study employs a quantitative approach using secondary data in the form of audited annual financial statements published on the Indonesia Stock Exchange during the 2020–2024 period. The population consists of 56 agricultural companies. Purposive sampling resulted in 13 companies being selected as the research sample, yielding a total of 65 observations. The analytical method used is panel data regression with the assistance of EViews 12. The results show that: (1) Biological Asset Intensity has a positive effect on Financial Performance; (2) Green Accounting Implementation has a negative effect on Financial Performance; and (3) Total Asset Turnover has a positive effect on Financial Performance.